Parental upbringing associated with drug use and mental health disorders in adolescent offenders - Avila Delgado, Ana Beatriz; D’Andrea, Gustavo; Alonso Castillo, María Magdalena; Gallegos, Maria Guadalupe; Delgadillo, Luz Maria; Orozco Gómez, Claudia (2018)
Aim: know the relationship between parental upbringing, drug use and mental health disorders in juvenile offenders. Methods: study cross-sectional and descriptive-correlational. The sample consisted of 49 juvenile offenders from the state of Zacatecas, Mexico. The scales applied were the Parental Perceived Styles Scale and the Massachusetts Youth Screening Instrument as well as open questions about drug use. Results: show that although a significant relationship was not found, we found associations between drug use and mental health disorders; and the substance preferred by teenage offenders was marijuana. Conclusion: Thus, early assessment nursing can identify changes in physical and mental health to offer strategies that promote healthy lifestyles and channel appropriate spaces of care to those who require specialized care.